BANK ASSETS, THEIR NATURE AND CONTENT - Raufov , Quvonchbek Xusin o‘g‘li (Educational Research in Universal Sciences, 2024)
This thesis aims to provide an in-depth analysis of bank assets, focusing on their nature, meaning and impact on financial stability. By examining their various types and characteristics, this study seeks to shed light on the challenges and opportunities that bank assets present to the global economy.